IMPLEMENTASI PEMBELAJARAN DARING DI TENGAH PANDEMI COVID-19 MENGGUNAKAN MEDIA GOOGLE CLASSROOM DAN ZOOM PADA PEMBELAJARAN PAI DI MAN 1 KABUPATEN TANGERANG - Sahabuz Zaeni Nur (QATHRUNÂ, 2021)
The purpose of this study is to describe the implementation of online learning in the midst of the Covid-19 pandemic using Classroom and Zoom at MAN 1 Kab. Tangerang and its supporting, inhibiting, and solution factors. This study uses a qualitative approach to understand the phenomena experienced by the research subjects holistically which are described in words and language in a special natural context and by utilizing various scientific methods. The research was conducted from January to d. April 2021. Data were obtained through interviews with informants who were considered to know the problems studied, which were 17 people, consisting of: 1 madrasah principal, 4 PAI subject matter teachers, 9 students, and 3 parents/guardians of students. Data were collected through observation, interview, and documentation techniques. The results of data analysis were carried out through data reduction activities, data display, and data verification. The results showed that: First, the online learning plan carried out by the teacher went through five stages, namely: 1) recognizing students and initial competencies, 2) setting learning goals/competencies to be achieved, 3) determining the learning platform used, 4) determining the material , methods, media, and learning resources, and 5) compiling online lesson plans. Second, the implementation of online learning through three steps, namely: 1) carrying out learning according to the lesson schedule, 2) ensuring the presence of students in learning, and 3) carrying out online learning based on the online lesson plans made. Third, the assessment of learning outcomes carried out by teachers refers to the technical guidelines issued by the Decree of the Director General of Education No. 2791/2020 concerning Assessment of Learning Outcomes, namely: 1) referring to the emergency technical guidelines from the Ministry of Religion of the Republic of Indonesia, 2) covering aspects of attitudes, knowledge, and skills, 3) designed to encourage meaningful learning activities and do not measure the completeness of overall curriculum achievements, 4) varies between students according to their respective conditions, 5) proportional / not excessive, and 6) scoring is done. Fourth, online learning can take place because of the support of several factors, namely 1) environmental conditions, 2) available internet network, 3) available internet quota, 4) motivation to master technology, 5) curiosity about online learning applications, and 6) family support. While the inhibiting factors are: 1) some students do not have a free internet network, 2) inadequate devices, 3) lack of mastery of learning applications, 4) lack of motivation, and 5) lack of parental support.